English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

equation:
f(x) = (3x) / (x-1)

i know i have to switch the "x" and "y", therefore giving me:

x = (3y) / (y-1)

now i'm stuck. do i cross multiply then factor? thanks for the help.

2006-11-16 08:35:17 · 2 answers · asked by shih rips 6 in Science & Mathematics Mathematics

2 answers

Now that you have the variables switched, you're supposed to solve for 'y' (where you have an equation that reads y=...), and that should give you the inverse of the original equation

2006-11-16 08:42:01 · answer #1 · answered by jeanneji 3 · 0 1

f(x) = (3x) / (x-1)
y=3x/(x-1) multiply by x-1
y(x-1)=3x distribute y
xy-y=3x subtract xy
-y=3x-xy associate x
-y=x(3-y) divide by 3-y
x=-(3-y)=y/(y-3)

2006-11-16 08:42:47 · answer #2 · answered by yupchagee 7 · 0 1

fedest.com, questions and answers